EXPLORing Arthritis with Total-body Positron Emission Tomography - Chaudhari, Abhijit J.; Abdelhafez, Yasser G.; Nardo, Lorenzo; Raychaudhuri, Siba P. (Seminars in Musculoskeletal Radiology, 2023)
Arthritis has significant adverse consequences on musculoskeletal tissues and often other organs of the body. Current methods for clinical evaluation of arthritis are suboptimal, and biomarkers that are objective and measurable indicators for monitoring of arthritis disease activity are in critical demand. Recently, total-body positron emission tomography (PET) has been developed that can collect imaging signals synchronously from the entire body at ultra-low doses and reduced scan times. These scanners have increased signal collection efficiency that overcomes several limitations of standard PET scanners in the evaluation of arthritis, and they may potentially provide biomarkers to assess local and systemic impact of the arthritis disease process. This article reviews current results from using total-body PET in the assessment of common arthritic conditions, and it outlines future opportunities and challenges.
Keywords: total-body positron emission tomography; rheumatoid arthritis; psoriatic arthritis; osteoarthritis; molecular imaging